Single Specialty Hospitals and Service Competition - Kathleen Carey; James F. Burgess; Gary J. Young (SAGE Publishing, 2009)
Advocates for physician-owned hospitals specializing in cardiac, orthopedic, and surgical services claim that these facilities induce healthy competition, stimulating improved performance among acute care hospitals. This paper examines the effect of specialty hospital entry on one indicator of competition among hospitals: changes in service provision by general hospitals in local markets. Results suggest that general hospitals are stepping up their own offerings of services that are in direct competition with those of specialty hospitals. Entry of specialty hospitals is also associated with significantly higher growth in high-technology diagnostic imaging services in the general hospitals in those markets.